THE FUNCTION OF HUMOR IN 19TH CENTURY BRITISH NOVELS (Лучшие интеллектуальные исследования, 2024)
This article examines the multifaceted role of humor in 19th-century British novels, arguing that it served not merely as entertainment but as a crucial tool for social commentary, character development, and narrative structure. Through analysis of key works by authors such as Jane Austen, Charles Dickens, and William Makepeace Thackeray, we explore how humor functioned to critique social norms, expose hypocrisy, and ultimately, enhance the reader's engagement with complex narratives and characters.